EFFICACY OF COMMUNICATORY TECHNOLOGIES IN MANAGEMENT OF PEDIATRIC SERVICE IN CONDITIONS OF PERSISTENT INCREASE OF QUALITY OF MEDICAL CARE - A.V. Shulaev; M.M. Sadykov; G.M. Khuzieva; А.R. Gainutdinov (Вопросы современной педиатрии, 2008)
The assessment of the efficacy of application of the modern communicatory technologies in children's city out patient clinics was presented in this article. Communicatory technologies in out patient clinics could help to solve three fundamental problems: medical, social and economical.Key words: communicatory technologies, children, children's out patient clinic, electronic outpatient's card.